Investigation of cytotoxic effects of Eugenia caryophyllus (Clove) - Ceylan Hepokur (Cumhuriyet University, 2018)
Objectives: Eugenia caryophyllus has been used as a traditional medicinal herb for thousands of years. It is used as an analgesic for tooth and toothache with the effect of eugenol substance included in clove. Clove is used at toothpaste and some mouthwash. The aim of this study was determined of in vitro cytotoxic effects Eugenia caryophyllus on fibroblast cells. Materials and Methods: Cytotoxic activity of Eugenia caryophyllus was evaluated using XTT assay. Results: In the present study, toxicity of clove that is used as a pain reliever in dentistry has examined on L929 cells. Eugenia caryophyllus were incubated at 24 and 48 hours.  The IC50 values of Eugenia caryophyllus (Clove) were found 57,92 ± 0,98 µg/mL in 24 h, 37,97 ± 0,74 µg/mL in 48h. Conclusions: The acceptable level of cytotoxicity associated with Eugenia caryophyllus requires further evaluation to be used